Barriers to English Listening Comprehension for Indonesian University Students: Implications for Listening Curriculum Development - Sri Wahyuningsih; Revanda Putri Salsabila (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
English has long been recognized as a crucial medium of international communication, serving not only educational purposes but also supporting career development. However, many students experience difficulties in understanding English expressions and sentences, a challenge that is particularly evident in listening comprehension among EFL students in Indonesia. Listening is widely regarded as one of the most difficult language skills for learners of English. This study aims to investigate the barriers faced by Indonesian university students in English listening comprehension and to explore the implications of these barriers for listening curriculum development. The data were collected through semi-structured interviews with eight students from Indonesian higher education institutions. The findings reveal that the main obstacles encountered by students include limited understanding of pronunciation and exposure to different accents, insufficient English vocabulary, poor clarity of audio input, and difficulty in comprehending fast speech rates. To enhance listening comprehension, students need continuous and repeated exposure to authentic listening materials, such as audio recordings from native speakers, English podcasts, speeches, motivational videos on YouTube, English songs, and movies. The implications of these findings for the development of an effective listening curriculum are discussed in this paper.